Synthesis, structures and magnetocaloric properties of two dinuclear GdIII clusters derived from monocarboxylate ligands. (27th July 2016) - Zheng, Teng-Fei; Cao, Chen; Dong, Piao-Ping; Liu, Sui-Jun; Wang, Feng-Feng; Tong, Xiao-Lan; Liao, Jin-Sheng; Chen, Jing-Lin; Wen, He-Rui
Graphical abstract: Two carboxylate-based Gd2 clusters have been constructed through hydrothermal reaction. They exhibit relatively large magnetocaloric effect with −Δ S m max  > 19.0 J kg −1  K −1 affected by relatively weak magnetic interactions and high magnetic density. Abstract: Two dinuclear Gd III clusters, namely [Gd2 (piv)6 (phen)2 ] (1 ) and {[Gd2 (2-TCA)6 (phen)2 ]·2H2 O} (2 ) (Hpiv = pivalic acid, 2-TCA = Thiophene-2-carboxylic acid and phen = 1, 10-phenanthroline), have been synthesized under hydrothermal conditions. Complex1 features dinuclear structure with two syn - syn - μ 2 - η 1 : η 1 carboxylates bridging, while2 exhibits dinuclear structure bridged by four carboxylates with syn - syn - μ 2 - η 1 : η 1 and syn - syn - μ 2 - η 1 : η 2 modes. Magnetic studies indicate that weak antiferromagnetic interactions between adjacent Gd III ions exist in1 and2 . They exhibit relatively large magnetocaloric effects with −Δ S m max  = 19.1 J kg −1  K −1 and 21.8 J kg −1  K −1 for Δ H  = 70 kOe, respectively, influenced by relatively high magnetic density and weak magnetic interaction.